Anxiety and care experiences in adolescents with chronic health conditions: an international, longitudinal study across the transfer of care - Alanen, Anna; Kallio, Mira; Culnane, Evelyn; Koivisto, Mari; Pasanen, Miko; Salantera, Sanna; Sawyer, Susan; Kosola, Silja (BMJ PUBLISHING GROUP, 2025)
Objectives To evaluate changes in anxiety, care experiences and condition impact among adolescents with chronic health conditions in two countries as they transfer to adult healthcare and to assess factors influencing anxiety levels.
Design A longitudinal international study. Data was collected by questionnaires before (2017-2021) and a year after (2018-2022) transfer of care.
Setting Two specialist hospitals in Finland and Australia.
Participants 440 adolescents with chronic health conditions were recruited from Finland (FIN n=237; mean age 17.2) and Australia (AUS n=203; mean age 18.3) with the answering percentage FIN 68.8% and AUS 55.2% of the first time point.
Main outcome measures The validated State-Trait Anxiety Inventory short form (STAI) was used to measure care-related anxiety. Care experiences were measured using eight questions from the Adolescent-Friendly Hospital Survey. Self-reported condition impact was measured by a Visual Analogue Scale. Care experiences, condition impact, country and age were included in regression analyses as predictors of care-related anxiety.
Results At baseline, there were few clinically meaningful differences between participants at the two sites. Adolescents reported positive care experiences both before and after the transfer of care. In regression analyses after the transfer of care, adolescents with lower condition impact experienced lower anxiety levels than adolescents with higher condition impact (beta -9.00, 95% CI -13.85 to 4.16, p<0.001). After the transfer of care, adolescents who reported negative care experiences also reported higher anxiety (median STAI score 40.0 (IQR 30.0-50.0) versus 33.3 (IQR 23.3-41.6), p<0.001).
Conclusion Across two different healthcare systems, most adolescents with chronic health conditions reported low anxiety and positive care experiences before and after transfer to adult healthcare. Beyond efforts to generally enhance positive care experiences, focusing on adolescents with higher-impact chronic conditions may reduce disease-related anxiety.